The importance and the adaptation of internal resources as a competitive advantage for the internationalization of food companies An analysis of Brazilian companies - Pigatto, Gessuir [UNESP]; Santini Pigatto, Giuliana Aparecida [UNESP]; Satolo, Eduardo Guilherme [UNESP]; Negreti, Amanda dos Santos [UNESP] (Emerald Group Publishing Ltd, 2019)
Purpose The purpose of this paper is to analyze how Brazilian food companies in the State of Sao Paulo determine the importance of and the need to adapt their internal resources as a competitive advantage for internationalization. Design/methodology/approach From a resource-based view (RBV), 35 different factors grouped into four categories were identified and presented to 24 companies. The data were analyzed through a gray relational analysis to establish all factors' order of importance. Findings Factors linked to human and organizational resources present greater adaptability and allow companies competitive and sustainable advantages but have not yet been explored thoroughly. Identifying and adapting internal resources do not guarantee achieving competitive and sustainable advantages, as the access to international market is also a consequence of commercial agreements developed by countries and economic blocks. Originality/value This paper stands out in the field of strategic management, specifically in the research on RBV, exportation and competitiveness, by making use of the theory of gray correlation system in an innovative and original way.
Keywords: Resource-based view; Internationalization; Food companies; Gray relational analysis; Food export; Competitiveness